The history of long‐term potentiation as a memory mechanism: Controversies, confirmation, and some lessons to remember. Issue 9 (22nd May 2020) - Dringenberg, Hans C.
ABSTRACT: The discovery of long‐term potentiation (LTP) provided the first, direct evidence for long‐lasting synaptic plasticity in the living brain. Consequently, LTP was proposed to serve as a mechanism for information storage among neurons, thus providing the basis for the behavioral and psychological phenomena of learning and long‐term memory formation. However, for several decades, the LTP‐memory hypothesis remained highly controversial, with inconsistent and contradictory evidence providing a barrier to its general acceptance. This review summarizes the history of these early debates, challenges, and experimental strategies (successful and unsuccessful) to establish a link between LTP and memory. Together, the empirical evidence, gathered over a period of about four decades, strongly suggests that LTP serves as one of the mechanisms affording learning and memory storage in neuronal circuits. Notably, this body of work also offers some important lessons that apply to the broader fields of behavioral and cognitive neuroscience. As such, the history of LTP as a learning mechanism provides valuable insights to neuroscientists exploring the relations between brain and psychological states.